Evolution by Sexual Selection - Petrie, Marion (Frontiers in Ecology and Evolution, 2021)
Charles Darwin published his second book “Sexual selection and the descent of man” in 1871 to try to explain, the evolution of the peacock’s train, something that he famously thought was problematic for his theory of evolution by natural selection. He proposed that the peacock’s train had evolved because females preferred to mate with males with more elaborate trains. This idea that a character could arise as a result of a female preference is still controversial. Some argue that there is no need to distinguish sexual from natural selection and natural selection can adequately explain the evolution of extravagant characteristics that are characteristic of sexually selected species. Here, I outline the reasons why I think that this is not the case and that Darwin was right to distinguish sexual selection as a distinct process. I present a simple verbal and mathematical model to expound the view that sexual selection is different from natural selection because, uniquely, it can simultaneously promote and maintain the genetic variation which fuels evolutionary change. Sexual selection can explain many other evolutionary problems that are characterised by having impossibly large costs and no obvious immediate benefits which have baffled evolutionary biologists for a very long time. If sexual selection does facilitate rapid adaptation to a changing environment as I have outlined, then it is very important that we understand the fundamentals of adaptive female choice and guard against any disruption to this natural process.